2014
DOI: 10.4161/19336918.2014.969139
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of High mobility group box 1 in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and is characterized as a typical inflammation-related carcinoma. High mobility group box protein 1 (HMGB1), a non-histone DNA-binding protein, is identified as a potent proinflammatory mediator when presents extracellularly. Recently, a growing body of evidence indicates that HMGB1 plays a potential role in HCC, but many questions remain unanswered about the relationship between HMGB1 and HCC formation and development. This review focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…A higher level of serum HMGB1 was reported to be correlated with larger tumor size, worse tumor stage, and pathological differentiation grades in these patients [32,38]. However, there has been no report investigating the usefulness of serum HMGB1 as a biomarker for advanced HCC patients who received treatment with sorafenib.…”
Section: Patients Treated With Haic Treatmentmentioning
confidence: 95%
See 2 more Smart Citations
“…A higher level of serum HMGB1 was reported to be correlated with larger tumor size, worse tumor stage, and pathological differentiation grades in these patients [32,38]. However, there has been no report investigating the usefulness of serum HMGB1 as a biomarker for advanced HCC patients who received treatment with sorafenib.…”
Section: Patients Treated With Haic Treatmentmentioning
confidence: 95%
“…A recent study reported that HMGB1 translocates to the cytoplasm and is then actively secreted by HCC cells; extracellular HMGB1 can then promote cancer invasion and metastasis through TLR-4 signaling [19]. Recent studies have also suggested that targeting HMGB1 production or release might be potential approaches for HCC treatment [19,32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1, secreted from hepatocytes in the process of liver inflammation such as NAFLD [47], also has been proven to promote HCC development [48]. Tsung et al demonstrated that HMGB1 could accelerate HCC progression through miR-21-mediated matrix metalloproteinase activity [49].…”
Section: Molecular and Signaling Network Disordersmentioning
confidence: 98%
“…The 3′-UTR of HMGB1 mRNA contains a complementary site for miR-548b ( Figure 4A), and this gene was chosen for validation because it has been implicated in hepatocarcinogenesis and cancer progression. [19][20][21][22][23][24][25][26][27][28][29][30][31] To test whether miR-548b can directly target the 3′-UTR of HMGB1 mRNA, wild-type and mutant luciferase plasmids were chemically synthesized and cotransfected with miR-548b mimics or the miR-548b inhibitor into Hep3B and SK-HEP-1 cells. MiR-548b overexpression in Hep3B cells decreased, whereas the miR-548b knockdown in SK-HEP-1 cells increased the luciferase activity of the plasmid harboring a wild-type miR-548b-binding site (P<0.05).…”
Section: Hmgb1 Mrna Is a Target Of Mir-548b In Hcc Cellsmentioning
confidence: 99%